A review on data center monitoring system using smart sensor network - G.M. Sharif Ullah Al-Mamun; Firuz Kabir; Fahima Nazeen; Jarin Sobah (Northern Negros State College of Science and Technology (NONESCOST), 2022)
A data center can be a single structure that contains computer systems or servers, as well as major elements including such storage and network communication systems, or a cluster of buildings that contain movable systems and related components (such as storage and telecommunications systems). All of the business area units' key operations are run on portable servers in the data center. Several environmental and security hazards can be addressed, and continuous services can be supplied to users, thanks to the data center's limitless observing conditions. Backup power, environmental management, and redundant data transfer connections are all included. The data center's security and privacy are critical in this instance. It is critical to avoid time periods in the data centre. Furthermore, as public awareness of environmental issues grows, data center energy consumption has risen to the top of the safety management priority list. Failures in the temperature and humidity functions will be significant. It is critical to pay strict attention to the data center's security at all times. Manual data center monitoring, on the other hand, is becoming increasingly time-consuming. Units in the technical field are currently emerging at a rapid pace. The data center is under the most strain in this instance. A good detector network, on the other hand, is critical to the advancement of Business 4.0 technology. As a result, we like to utilize a good network of detectors for data center observation protection and privacy. The Internet of Things is frequently utilized for data center observation, as well as a good wireless detector network. A wireless detector system is employed in this paper to track the effectiveness of adjustments in real time.